One Health approach on human seroprevalence of anti-Toxocara antibodies, Toxocara spp. eggs in dogs and sand samples between seashore mainland and island areas of southern Brazil - Ruana Renostro Delai (Elsevier, 2021)
Toxocariasis, caused by Toxocara spp. nematodes, is among the top 5 neglected parasitic diseases worldwide; however, no comprehensive study to date has serologically compared infections in people and their dogs and environmentally contaminated soil or sand of mainland and island locations. Accordingly, this study aimed to assess the seroprevalence of anti-Toxocara antibodies in traditional human seashore populations, the presence of eggs in dogs' feces and hair, and the presence of eggs in environmental samples from islands compared to the adjacent mainland of southern Brazil. Overall, 212/328 (64.6%) people were positive for Toxocara spp. antibodies, including 125/190 (65.8%) island and 87/138 (63.0%) mainland residents. For dog samples, 12/115 (10.43%) were positive for the presence of Toxocara spp. eggs, all from dogs living in islands, and 22/104 (21.15%) dog hair samples contained eggs of Toxocara spp. Environmental contamination with Toxocara spp. eggs was observed in 50/130 (38.46%) samples from all sampled sites. No significant association was found between risk factors (age, sex, educational level, monthly income, owning dogs or cats, ingestion of treated water, and consumption of raw or uncooked meat) and Toxocara spp. seropositivity. The present study is the first concurrent report on people, their dogs, and environmental contamination of Toxocara spp. The high prevalence we observed in the seashore populations of both in island and mainland areas may be caused by exposure to contaminated sand and climatic factors favoring frequent exposure to Toxocara spp. In conclusion, seashore lifestyle and living conditions of both island and mainland areas may have predisposed higher contact with infected pets and contaminated soil, favoring the high prevalence of toxocariasis.